INFLUENCE PERCEIVED VALUE AND SOCIAL MEDIA MARKETING TOWARDS REPURCHASE INTENTION WITH SATISFACTION AS AN INTERVENING VARIABLE (AT PLAYDATE FASHION STORE KEMANG JAKARTA) - Sholeha, Amialia; Vania, Amelindha (JURNAL EKBIS, 2025)
This study aims to examine the variables that influence customer value, marketing in social media, customer satisfaction in orders to create repeat purchases at Playdate Kemang. The type of research used is quantitative with an explanatory approach. Primary data in this study utilizes questionnaire data distributed via gform. The population in this study were female workers in the manufacturing sector in Pasuruan and a sample of 90 respondents. By using probability sampling technique and using Malhotra's formula. The data was analyzed and tested using the SPLS 4 application Based on the results of the study showed that: (1). The variable perceived value has a significant effect on repurchase intention at Playdate Kemang. (2). Social media marketing variables have a significant effect on repurchase intention at Playdate Kemang. (3). The satisfaction variable has a significant effect on repurchase intention at Playdate Kemang. (4). The perceived value variable has a significant effect on satisfaction at Playdate Kemang. (5). Social media marketing variables have a significant effect on satisfaction at Playdate Kemang. (6). The satisfaction variable mediates perceived value on satisfaction at Playdate Kemang. (7). The satisfaction variable mediates social media marketing on satisfaction at Playdate Kemang.